IMPLEMENTATION OF THE MERDEKA CURRICULUM ON THE DEVELOPMENT OF PANCASILA CHARACTER OF STUDENTS IN INDONESIA - Zakki, Ahmad; Firman, Firman; Bin Che Amat, Muhammad Asyraf (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Education aims to develop the potential that exists in each individual. In addition to developing the cognitive aspects of students, education also plays a role in the formation of ethical character in accordance with Indonesian culture based on Pancasila. This paper aims to find out that the merdeka curriculum implements Pancasila character values to students in the aspect of character development. This research uses a naturalistic approach with data collection methods through literature study and analyzed using descriptive. Primary data comes from scientific articles indexed in sinta journals with the latest publications in the last 10 years, and electronic books. The results obtained that Pancasila character education is contained in the Pancasila student profile project which develops the character of faith and piety to God Almighty, and has noble character, global diversity, independence, mutual cooperation, critical and creative reasoning.